DESIGNING ACCOUNTING SOFTWARE BASED ON MICROSOFT ACCESS AT CV BADAI ARTA PERMATA - Muhammad Taufik; Gideon Benhans (Universitas Internasional Batam, 2022)
CV Badai Arta Permata’s accounting bookkeeping activities still apply manual recording which can cause the project report and financial report not to provide relevant information such as cost by project, profit or loss statement by the project. This community service aims to generate bookkeeping software as per transactions that have occurred at CV Badai Arta Permata. In collecting information, the author uses the method of observation and interview. We use evidence of transactions based on the business operations as our reference to generate bookkeeping software that uses Microsoft Access. The output of bookkeeping software includes an account list, supplier list, customer list, and ledger. Moreover, transactions output includes general journal form, adjusting journal form, purchase form, sales form, receipt form, payment form. After bookkeeping, we generate a system around financial reports such as a statement of profit or loss, statement of financial position, purchase report, sales report. We contribute to providing the information of cost by project, profit or loss by the project.